Analysis of critical residues for peroxygenation and improved peroxygenase activity via in situ H2O2 generation in CYP105D18 - Pardhe, Bashu Dev; Oh, Tae-Jin (Frontiers in Microbiology, 2023)
Limited numbers of CYPs have been reported to work naturally as peroxygenases. The peroxide shunt pathway can be efficiently used as an alternative for the NAD(P)H and reductase systems, particularly in high hydrogen peroxide (H2O2) resistance CYPs. We reported the structural and biochemical features of CYP105D18 peroxygenase for its high H2O2 tolerance capacity. Q348 was a crucial residue for the stability of CYP105D18 during the exposure to H2O2. In addition, the role of the hydrophilic amino acid T239 from the I helix for peroxygenation and regiospecificity toward testosterone was investigated. Interestingly, T239E differs in product formation from wild type, catalyzing testosterone to androstenedione in the presence of H2O2. The other variant, T239A, worked with the Pdx/Pdr system and was unable to catalyze testosterone conversion in the presence of H2O2, suggesting the transformation of peroxygenase into monooxygenase. CYP105D18 supported the alternative method of H2O2 used for the catalysis of testosterone. The use of the same concentration of urea hydrogen peroxide adducts in place of direct H2O2 was more efficient for 2β-hydroxytestosterone conversion. Furthermore, in situ H2O2 generation using GOx/glucose system enhanced the catalytic efficiency (kcat/Km) for wild type and F184A by 1.3- and 1.9-fold, respectively, compared to direct use of H2O2 The engineering of CYP105D18, its improved peroxygenase activity, and alteration in the product oxidation facilitate CYP105D18 as a potential candidate for biotechnological applications.